2022
DOI: 10.7150/ijms.77729
|View full text |Cite
|
Sign up to set email alerts
|

DPA promotes hBMSCs osteogenic differentiation by miR-9-5p/ERK/ALP signaling pathway

Abstract: Docosahexaenoic acid (DHA) has been reported potentiate osteogenic differentiation, while Docosapentaenoic acid (DPA), another Omega-3 fatty acid, its contribution to the osteogenic differentiation of human bone-marrow-derived mesenchymal stromal cells (hBMSCs) is not entirely elucidated. The Alizarin Red S (ARS) staining and the expression of osteogenesis-associated genes were analyzed during osteogenic induction by DPA. Then, bioinformatics analysis and dual luciferase reporter assays were investigated to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…This suggests that miR-9-5p may have a representative role in the immunomodulation of hydatid disease. Previous studies have shown that miR-9-5p can promote the anti-inflammatory effects of MSCs, inhibit osteogenic differentiation and mineralization of osteoblast lineage cells, and promote osteoclastogenesis through the activation of the SIRT1/NFκB signaling pathway ( Zhang L. et al, 2021 ; Gao et al, 2022 ; He et al, 2022 ). This indicates that miR-9-5p has the potential to modulate immunosuppression and regulate the osteogenic/osteoclastic balance in hydatid disease.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that miR-9-5p may have a representative role in the immunomodulation of hydatid disease. Previous studies have shown that miR-9-5p can promote the anti-inflammatory effects of MSCs, inhibit osteogenic differentiation and mineralization of osteoblast lineage cells, and promote osteoclastogenesis through the activation of the SIRT1/NFκB signaling pathway ( Zhang L. et al, 2021 ; Gao et al, 2022 ; He et al, 2022 ). This indicates that miR-9-5p has the potential to modulate immunosuppression and regulate the osteogenic/osteoclastic balance in hydatid disease.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, the quantification of ALP and RUNX2 has relied on laborious and often expensive techniques, including enzyme-linked immunosorbent assays (ELISAs) [20,21], Western blotting [22,23], and polymerase chain reaction (PCR) [24,25]. These methods, while valuable for research, are impractical for rapid, point-of-care diagnostics or realtime monitoring of osteogenic processes.…”
Section: Introductionmentioning
confidence: 99%